Analisis Ekspresi Fibroblast Activation Protein (FAP) terhadap Faktor Klinkopatologi dan Respon Kemoterapi pada Tumor Ganas Epitelial Ovarium - Yunike Rinelda; Wresnindyatsih; Aida Farida Farida (Majalah Patologi Indonesia, 2021)
BackgroundEpithelial ovarian carcinoma is the most common cause of death among gynecological malignancies in the women. The interactionamong cancer cells and tumor microenvironment plays roles in cancer proliferation and invasiveness. One of important component oftumor microenvironment that could stimulate tumor proliferation and invasiveness, is fibroblast. Activated fibroblasts also known ascarcinoma associated fibroblasts (CAFs). The purpose of research is to analyzed FAP expressions to clinicopathologic characteristic(histopathology subtype and clinical stadium of FIGO) and chemotherapeutic responses.MethodsThis study is a retrospective observational analytic study with cross-sectional designs was undertaken during January 1, 2016 to June30, 2018. The sample was 55 paraffin block sample epithelial ovarian carcinomas consists of 11 samples for each histopathologysubtype collected used purposive sampling technique. All samples were immunostained with FAP antibody. FAP expressions wasevaluated based on Min Shi et al studies. It analyzed stained area/ proportion (P) and intensity (I). Statistical analysis using chi-squarewas performed using SPSS version 17.ResultsPatients of 40-49 years old (24; 43.6%), clinical stadium is III (30; 54.5%), Complete response (CR) of chemotherapeutic response(38; 69.1%). The statistic analyses between histopathology subtypes (p=0.038), clinical stadium of FIGO (p=0.000) and chemotherapyresponse (p=0.000) showed significant differences.ConclusionFAP expressions could showed correlation between clinicopathologic characteristic (histopathology subtype and clinical stadium ofFIGO) and chemotherapeutic response.